2022
DOI: 10.1590/2175-8239-jbn-2021-0126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vegetarian diets on renal function in patients with chronic kidney disease under non-dialysis treatment: A scoping review

Abstract: Vegetable protein diets (VPDs) in chronic kidney disease (CKD) patients may be related to beneficial biological actions and possibly clinical impact. This is a scoping review that merge studies that evaluated the effect of a vegetarian diet on kidney function in adults with CKD under non-dialysis treatment. The evaluated outcome was the impact in renal function assessed by eGFR or creatinine clearance. MEDLINE (accessed by PubMed) was searched up to September 8, 2020. Data were extracted by two independent rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…The other three studies (one cross-sectional study and two cross-over trials) did not show differences in renal function (measured parameters: eGFR or creatinine clearance) with vegan and meat-based diets [Chang et al, 2018;Moe et al, 2011;Soroka et al, 1998]. However, two of these studies (both cross-over design studies) included a very small sample size of only 8-9 participants; therefore, the meaning results may be limited [Moe et al, 2011;Soroka et al, 1998;Valim et al, 2022].…”
Section: Vegetarian Diet and Chronic Kidney Diseasementioning
confidence: 96%
See 1 more Smart Citation
“…The other three studies (one cross-sectional study and two cross-over trials) did not show differences in renal function (measured parameters: eGFR or creatinine clearance) with vegan and meat-based diets [Chang et al, 2018;Moe et al, 2011;Soroka et al, 1998]. However, two of these studies (both cross-over design studies) included a very small sample size of only 8-9 participants; therefore, the meaning results may be limited [Moe et al, 2011;Soroka et al, 1998;Valim et al, 2022].…”
Section: Vegetarian Diet and Chronic Kidney Diseasementioning
confidence: 96%
“…In addition to this meta-analysis, there is one randomized controlled trial, two cross-over studies, and one cross-sectional study that tested vegetarianism's effect in the groups of non-dialyzed patients with CKD [Valim et al, 2022]. A prospective, randomized, controlled trial of 207 participants showed that a very-low-protein vegetarian diet (VLPD; 0.4 g/kg/day) combined with amino acid ketoanalogues supplementation was more beneficial than a traditional low-protein diet (LPD; 0.6 g protein/kg/day) [Garneata et al, 2016].…”
Section: Vegetarian Diet and Chronic Kidney Diseasementioning
confidence: 99%
“…On the other hand, an omnivore diet that focuses on lean protein sources, whole grains, fruits, and vegetables while moderating the consumption of red and processed meats can also support kidney health and minimize the risk of uremia-related complications. Individual preferences, nutritional needs, and consultation with healthcare professionals are essential considerations when choosing a dietary approach for individuals with kidney disorders like AKI, CKD, or ESRD [ 67 , 68 , 69 ].…”
Section: Lifestyle Dietary Habits and Uremic Toxicitymentioning
confidence: 99%